Epitaxial growth: rapid synthesis of highly permeable and selective zeolite-T membranes. Issue 34 (16th August 2017) - Luo, Yiwei; Lv, Youjia; Kumar, Prashant; Chu, Jingjing; Yang, Jianhua; Tsapatsis, Michael; Mkhoyan, K. Andre; He, Gaohong; Lu, Jinming; Zhang, Yan
Abstract : Rapid synthesis of highly permeable and selective zeolite T membranes was achieved through epitaxial growth. Abstract : Dense and continuous zeolite T membranes with controlled membrane thickness similar to that of the seed layer can be obtained on both macroporous Al2 O3 tubes and hollow fibers with a largely shortened synthesis time through epitaxial growth of seeds and closing of voids among seeds, exhibiting a high flux of 5.9 and 9.8 kg m −2 h −1 with corresponding selectivity larger than 10 000 and 3870 for a 90% isopropanol/water mixture at 348 K.